A View from the Bridge, de Arthur Miller: uma peça com traços épicos e questões sociais (Macarthismo) - Silva de Oliveira, Éwerton (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article has as an objective to find the epic elements which are present in Arthur Miller’s (1915-2005) A View from the Bridge (1955-6). By using theories such as Rosenfeld’s (2006) and Szondi’s (2001), discussing Brecht’s Epic Theater – which is exemplary in terms of epic resources usage – and analyzing the American play, it was possible to discover that the more Miller tries to discuss social issues such as McCarthyism, the more the dramatic form of A View from the Bridge pre- sents structural changes, and epic elements start to appear in the play, such as the presence of Alfieri, the lawyer-narrator who tells and comments the story of a long- shoreman called Eddie Carbone. These epic traces help in the theatrical representa- tion and in the discussion of social problems – especially the ones of 1950’s USA.